Role of Reactive Oxygen Species during Cell Expansion in Leaves. Issue 4 (28th October 2016) - Schmidt, Romy; Kunkowska, Alicja B.; Schippers, Jos H.M.
Abstract : Reactive oxygen species as potent regulators of leaf development poses special interest for cell expansion.